2021
DOI: 10.1093/infdis/jiab337
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Diagnostic Test Performance Over the Course of Acute SARS-CoV-2 Infection

Abstract: Background Serial screening is critical for restricting spread of SARS-CoV-2 by facilitating the timely identification of infected individuals to interrupt transmission chains. The variation in sensitivity of different diagnostic tests at different stages of infection has not been well documented. Methods This is a longitudinal study of 43 adults newly infected with SARS-CoV-2. All participants provided daily samples for sali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 11 publications
3
127
0
1
Order By: Relevance
“…Finally, we examined the relationship between viral culture and antigen FIA results in vaccinated (fully plus partially) and newly vaccinated individuals (Fig 1G) . We observed that vaccinated and newly vaccinated participants tested positive by antigen FIA on 78% and 85% of the days on which they also tested positive by viral culture, suggesting that antigen FIA can be used to identify vaccine breakthrough infections with high transmission risk, especially if used as part of a serial screening program 9 . These results are consistent with our previous results in unvaccinated individuals as well as earlier cross-sectional studies examining the relationship between antigen tests positivity and infectious virus shedding 7,10,11 .…”
Section: Main Textmentioning
confidence: 92%
“…Finally, we examined the relationship between viral culture and antigen FIA results in vaccinated (fully plus partially) and newly vaccinated individuals (Fig 1G) . We observed that vaccinated and newly vaccinated participants tested positive by antigen FIA on 78% and 85% of the days on which they also tested positive by viral culture, suggesting that antigen FIA can be used to identify vaccine breakthrough infections with high transmission risk, especially if used as part of a serial screening program 9 . These results are consistent with our previous results in unvaccinated individuals as well as earlier cross-sectional studies examining the relationship between antigen tests positivity and infectious virus shedding 7,10,11 .…”
Section: Main Textmentioning
confidence: 92%
“…Four surveillance studies were conducted in Greece, Switzerland, USA, and the Netherlands, which used Ag-RDTs to monitor COVID-19 across an entire town, primary and secondary schoolchildren and teachers, university students and staff, and in professional football clubs, respectively. 41-44…”
Section: Resultsmentioning
confidence: 99%
“…Accounting for time-since-onset is therefore advisable regardless. Other instances where epidemic dynamics will not affect viral load comparisons are when samples are obtained longitudinally from the same individuals, allowing the comparison of the full viral kinetics curve [20,35], or obtained near the time of exposure such that all samples have a similar time-since-infection [36].…”
Section: Discussionmentioning
confidence: 99%